2017
DOI: 10.1371/journal.pone.0179109
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review evaluating the psychometric properties of measures of social inclusion

Abstract: IntroductionImproving social inclusion opportunities for population health has been identified as a priority area for international policy. There is a need to comprehensively examine and evaluate the quality of psychometric properties of measures of social inclusion that are used to guide social policy and outcomes.ObjectiveTo conduct a systematic review of the literature on all current measures of social inclusion for any population group, to evaluate the quality of the psychometric properties of identified m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 127 publications
1
85
0
5
Order By: Relevance
“…Despite the fact that social inclusion is often cited as an important treatment outcome by mental health service users, it is often neglected by mental health professionals when considering care planning [7,12]. One factor contributing to this may be the lack of a validated, robust, and acceptable measure of social inclusion for use in mental health services [2,4,13,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that social inclusion is often cited as an important treatment outcome by mental health service users, it is often neglected by mental health professionals when considering care planning [7,12]. One factor contributing to this may be the lack of a validated, robust, and acceptable measure of social inclusion for use in mental health services [2,4,13,14].…”
mentioning
confidence: 99%
“…A number of measures have been developed that assess related concepts, such as social integration, social networks, and quality of life, or which represent composite measures, created from a selection of questions and subscales [13]. However, reviews of existing measures of social inclusion for individuals with mental health problems have concluded that, despite recent developments, further progress is required [14].…”
mentioning
confidence: 99%
“…The SCS-R is an 8-item measure rated on a 5-point scale from (1 = "Strongly disagree" to 5 = "Strongly agree") with statements where lower scores indicated feeling more socially connected (e.g., "I feel so distant from people"). This scale has shown good psychometric properties demonstrating strong content validity and good structural validity (Cordier et al, 2017). High internal consistency has also been met (α = .91) (Lee & Robbins, 1995), which is similar to that found by Kleynshteyn (2013) with a clinical sample.…”
Section: Methodssupporting
confidence: 79%
“…Striving to obtain a sense of belonging is said to form part of our occupational nature, as the most complex occupations require collaboration and sharing of skills with others (Sadlo, 2016). Becoming involved in community based groups or organisations has been suggested as a way of increasing a sense of belonging (Cordier et al, 2017). This suggestion was supported by our study, as a sense of belonging and of community as a result from engaging in occupations relating to community based volunteering, was a strong theme that emerged from the Rotarian focus group in phase one.…”
Section: Belongingmentioning
confidence: 99%